Riscos ocupacionais e agravos à saúde em coletores de lixo: revisão integrativada literatura - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Visceral leishmaniasis (VL), is classified as a zoonotic disease commonly known as kala-azar, potentially fatal to humans, affects people of all ages, but most of the disease recorded in endemic areas are in children under 10 years old, in which both environmental factors and socioeconomic conditions are related. Classified by the Health Organization (WHO) as a neglected tropical disease, leishmaniasis are the only ones still growing, and Brazil is the country with the highest number of cases of the three forms of leishmaniasis in the American continent: cutaneous, mucocutaneous and the visceral. The State of Pará has been shown to be an endemic area of visceral leishmaniasis and today, however, it is essential to obtain data regarding the spread of VL infection in the State Objectives: To evaluate the epidemiological profile of patients with Leishmaniasis Visceral in the State of Pará, from 2010 to 2019. Methodology: cross-sectional study of statistical and epidemiological data collected on the DATASUS website. Results: There was an increase in cases of VL in the reference period, the age group most affected by the disease are children between 0 and 9 years old and adults between 20 and 50 years old, who usually have a level of schooling fundamental, sometimes incomplete. It was also observed the predominance of the cure of the reported patients, and the predominance of the disease in brown and white people, and to a lesser extent in indigenous and yellow people, and also the predominance of the disease in male people. Conclusion: The present work showed that VL in the State of Pará, in the period from 2010 to 2019, showed a tendency to expand only in the Health Region of Carajás, and in the period from 2010 to 2017 in the Health Region of Araguaia, tending to fall. the numbers of cases in later years. Predominance of cases in brown and male people, with predominantly elementary school education. Presenting an even higher incidence in children.
Keywords: Coleta de resíduos sólidos; Riscos ocupacionais; Limpeza urbana